(untitled) (Scientific journal of the Fergana State University, 2026)
This article provides a comprehensive analysis of the historical development of social stratification, its evolutionary stages, and the new forms it takes in contemporary society. It explores economic, political, and cultural transformations that have reshaped social layers, as well as the influence of digital transformation and the knowledge economy on the emergence of new social groups. The study also examines how global trends, technological innovations, migration, and labor market transformations contribute to modern patterns of social inequality and stratification mechanisms.